Analysis of Dust Concentration, NO2 Concentration, and Pulmonary Disfunction on Woman's Sweeper in Jalan Ahmad Yani Kota Surabaya - Zaen, Bagus Syahru (JURNAL KESEHATAN LINGKUNGAN, 2018)
The lung's function status is measured by the spirometer & known through value of Forced Vital Capacity (FVC) and Forced expiratory volume in one second (FEV1). The study aims was to analyze dust and NO2 concentration in ambient and the pulmonary disfunction of woman sweeper in Jalan Ahmad Yani Kota Surabaya. This research was a descriptive with cross sectional design. The research sample was 10 persons who were working as woman's sweeper in the Jalan Ahmad Yani Kota Surabaya. The variables were the dust and NO2 concentration, individual charactheristics such as age, workdays duration, workyears period, using of Personal Protective Equipment (masks), passive smoker, and body mass index. The study was using interview, pulmonary function test using spirometer, measurement of dust concentration using EPAM 5000, and NO2 concentration using Gravimetry. The result showed that dust concentration on the third location was 1.33 mg/m3 and NO2 concentration on the first location was 103.6 Î¼g/m3. Both of these parameters were above the standard of Peraturan Gubernur Jawa Timur No. 10 tahun 2009. The pulmonary function test was 6 of 10 respondents had pulmonary disfunction which is mild restriction. It was recommended to wear clean mask for woman's sweeper while working and to consider the workdays duration.